Maritime Trade Routes in the Arab Islamic State - Prof. Dr. Alaa Oraiby Sabaa (Journal of College of Education, 2025)
This study aims to shed light on the diverse maritime trade routes of the Arab Islamic State, which spanned from the Arabian Gulf and the Indian Ocean in the east to the Mediterranean Sea and Africa in the west. The research draws upon historical sources such as the works of Al-Masudi and Ibn Khordadbeh, alongside a detailed geographical analysis of key ports-including Siraf, Aden, and Oman-that served as pivotal hubs for commercial exchange with India, China, and East Africa. Furthermore, the study examines advanced navigational techniques, such as the strategic use of monsoon winds, and explores the role of this maritime network in disseminating Islamic culture and bolstering the global economy over centuries of prosperity.